2011
DOI: 10.1080/09712119.2011.621533
|View full text |Cite
|
Sign up to set email alerts
|

The effects of modified atmosphere packaging on goat kid meat quality

Abstract: Forty goat kid carcass ribs were used to determine the effects of three different package methods (air, vacuum and modified atmosphere packaging Á (MAP Á) 30:30:40 mixture of N 2 :O 2 :CO 2 ) on meat carcasses which were held for 9 days in storage conditions (48C). Instrumental colour (L*a*b*), final pH, water holding capacity (WHC), water loss and sensorial odour and colour were recorded at 1, 3, 5, 7 and 9 days. L* value increased statistically during the experimental period in vacuum and MAP. Either the pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Hence, L à is the most important CIE L à a à b parameter used for the consumer judgement of light suckling kid meat (Ripoll et al 2018a). This meat is characterised by high L à and h ab and low C à ab (Morales-De la Nuez et al 2011;De Palo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, L à is the most important CIE L à a à b parameter used for the consumer judgement of light suckling kid meat (Ripoll et al 2018a). This meat is characterised by high L à and h ab and low C à ab (Morales-De la Nuez et al 2011;De Palo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, Ozcan et al 37 studied the meat color of Gokceada suckling kids raised extensively and concluded that while a* and b* seemed not to change from day 1 to day 5, L* decreased slightly. Morales-De la Nuez et al 34 did not report changes in L* and a* of meat from Majorera kids stored for 7 days; however, b* and h ab increased while C ab * decreased. Changes in h ab and C ab * with storage time can be a result of the oxidation of myoglobin to metmyoglobin and the loss of heminic pigments due to the freeze/thaw process.…”
Section: Discussionmentioning
confidence: 88%
“…studied the meat color of Gokceada suckling kids raised extensively and concluded that while a * and b * seemed not to change from day 1 to day 5, L * decreased slightly. Morales‐De la Nuez et al . did not report changes in L * and a * of meat from Majorera kids stored for 7 days; however, b * and h ab increased while C ab * decreased.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, in recent years other factors have been studied, including nutrition (Lo´pez et al 2010;Montano et al 2010; Argu¨ello 2011) and ageing time (Priolo et al 2001;Morales-delaNuez et al 2009;Merera et al 2010;Morales-delaNuez et al 2011), that can dramatically affect meat quality. Throughout the meat-producing industry, the use of energetic feedstuffs to supplement pasture diets for limited periods, or for finishing purposes, is becoming more common.…”
mentioning
confidence: 99%